Women at the Frontline of Survival: Lessons Learned from Deployment Portable Ultrasound in Disaster-Affected Highland Communities in Bener Meriah, Aceh - Kosim, Maryami Yuliana; Shinta, Laily Anna Diah Ardi; Rahman, Muhammad Nurhadi; Darsan, Herri; Sutono, Sutono (Universitas Gadjah Mada, 2026)
Introduction: Disasters exacerbate gender-based vulnerabilities while underscoring women’s critical role in sustaining community health systems. In Aceh, disaster-related damage to infrastructure disrupted access to essential maternal and reproductive health services. Objective: This study reports lessons learned from the deployment of portable ultrasound (USG) within a mobile disaster health response in Bener Meriah, Aceh, focusing on women’s intersecting vulnerability and agency. Methods: A descriptive lessons-learned design was applied using service logs, field observations, team debriefings, and informal discussions with affected women and community midwives during a Universitas Gadjah Mada–led response. Portable USG was integrated into community-based midwifery networks to support point-of-care assessments in isolated areas. Results: Disrupted transportation and damaged health facilities significantly limited access to care. Mobile services using portable USG reduced geographic and mobility barriers, enabled timely assessments, and strengthened trust in health services. Community midwives played a central role in outreach, service delivery, and continuity of care. Conclusion: Disaster health responses are more effective when mobile health technologies are embedded within trusted community-based female health worker networks, reinforcing women’s roles in equitable and resilient health systems.